Effect of solution concentration and temperature on the growth of ferromagnetic nanowires during electrodeposition - Samykano, M.; Rahman, M. M.; Nurul Akmal, Che Lah; Ngui, Wai Keng; Ramli, Junid
The present research and dissertation focuses on: 1. Experimental synthesis of electrodeposited Ni nanowires at different solution concentration and temperature, 2. Physical properties characterization of the synthesized nanowires to understand their morphology, structural and crystallographic properties. Key research insights from the present experimental research include: Electrodeposition method consistently synthesizes high purity Ni nanowires with a significant improvement in surface morphology when optimum value of solution concentration applied, during synthesis; X-ray diffraction (XRD) characterization and analysis indicate that solution concentration and heating temperature has significant influence on the crystal orientation of Ni nanowire.